2016
DOI: 10.1128/mbio.00273-16
|View full text |Cite
|
Sign up to set email alerts
|

Completion of the Entire Hepatitis C Virus Life Cycle in Vero Cells Derived from Monkey Kidney

Abstract: A hepatitis C virus (HCV) cell culture system incorporating the JFH-1 strain and the human hepatoma cell line HuH-7 enabled the production of infectious HCV particles. Several host factors were identified as essential for HCV replication. Supplementation of these factors in nonhepatic human cell lines enabled HCV replication and particle production. Vero cells established from monkey kidney are commonly used for the production of vaccines against a variety of viruses. In this study, we aimed to establish a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
0
23
0
2
Order By: Relevance
“…A recent report by Yu et al (63) showed that an HCV chimera including the region upstream of domain II of EHcV propagated in a miR-122-independent manner (63), which supports our data. The tissue tropism of HCV is likely determined by miR-122, because exogenous expression of miR-122 enhanced the replication of HCV in nonhepatic cells (55)(56)(57). Although the liver tropism of EHcV is observed in horses (20), the involvement of miR-122 in liver tropism remains debatable, because infection of canine respiratory organs by EHcV has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report by Yu et al (63) showed that an HCV chimera including the region upstream of domain II of EHcV propagated in a miR-122-independent manner (63), which supports our data. The tissue tropism of HCV is likely determined by miR-122, because exogenous expression of miR-122 enhanced the replication of HCV in nonhepatic cells (55)(56)(57). Although the liver tropism of EHcV is observed in horses (20), the involvement of miR-122 in liver tropism remains debatable, because infection of canine respiratory organs by EHcV has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…miR-122 represents the majority of microRNA in hepatocytes and is expressed rarely in other tissues (54). Nonhepatic cells exogenously express miR-122, which permits efficient HCV replication (55)(56)(57). Expression of miR-122 may contribute to the liver tropism of HCV.…”
mentioning
confidence: 99%
“…It is not known how HCV would evolve if left unperturbed while replicating for a long time in the same cellular environment. Such exploration can be carried out due to the availability of effective cell culture systems to replicate the complete HCV genome (29)(30)(31)(32). Adaptive mutations have been identified in infectious HCV clones or subgenomic replicons upon multiplication in cell culture (33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…Immunostaining of infected cells was performed as previously described (38). For the subcellular localization analysis, 1 g of the V5-tagged NS3 and/or HA-tagged NS4A expression plasmid was transfected into 3 ϫ 10 5 Huh-7.5.1 cells using the Lipofectamine 2000 reagent (Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%